A Model for Evaluating Program Costs: A General View - Vallerand, Noel (Canadian Journal of Higher Education, 1977)
The university accepts the responsibility of educational programs, carries out research programs and offers programs in diverse areas to the community at large. In order to do this, the university requires human and physical resources which, without taking into con-sideration their intrinsic value, are all translated into financial resources. It follows logically that this requires an allocation of resources for the different programs which takes into account the development priorities which the very implantation of the programs tries to reveal. But the process which consists of foreseeing the rational allocation of resources is extremely delicate, as much on the level of political significance, internal and external, as on the technical level which consists of focussing on the tools required for a new reading of budgetary reality.